Beneficial effect of Danggui-Shaoyao-San, a traditional Chinese medicine, on drowsiness induced by chronic restraint stress. (15th June 2015) - Zhou, Kecheng; Jia, Nati; Jiang, Nan; Wang, Feng; Kou, Junping
Highlights: CRS increases the sleeping time and decreases the sleep latency. CRS changes the locomotion ability and emotional state of mice. CRS decreases body weight and food intake of mice. DSS reverses CRS induced stress related disorders, especially for sleep disorder. Abstract: Danggui-Shaoyao-San (DSS), a famous Chinese complex prescription, has a long history of treating dysmenorrhea in China. Recent studies showed that DSS had its therapeutic efficacy on depression. In the present study, the effects of aqueous extract of DSS were examined to investigate the pharmacological basis for its therapeutic efficacy on chronic restraint stress (CRS)-induced sleep disorder. Mice were treated with DSS by gavage administration at doses of 0.625 g/kg, 1.25 g/kg and 2.5 g/kg for 10 days. Sleep time and sleep latency were measured 24 h after the CRS procedures using the sodium pentobarbital-induced sleep test. Open field test was used to evaluate the mice locomotion and anxiety/depression levels. Body weight and food intake were determined as well. The results showed that DSS dose-dependently prolonged latency and decreased sleep time of CRS mice, reversed CRS-induced decrease of mean velocity, the percentage of center distance and time in central area, as well as decreased body weight and food intake. In conclusion, our results suggest that DSS has exerted measurable therapeutic effects in hypersomnia induced by chronic restraint stress.